Power, sexuality and subversion in Lutsango and Siswati traditional wedding songs - Dlamini, Nonhlanhla (My University, 2009)
I. ABSTRACT As a critical field, Anthropology aims to study humankind in all its diversity: past, present and future, physical, psychological, cultural and social, etc. Lienhardt (1967: 1) says, social anthropology “is connected with older and more familiar subjects, particularly with history and sociology, and cannot be neatly distinguished from them”. However, Anthropology has come a long way since the 19th century when the story of modern anthropology begun. During this period, the notion for human progress became the guiding light for anthropological thought. The early anthropological school of this thought contributed to the notion of racial superiority as one can notice that it was around this time that the theory of racial determinism was proposed to account for the differences among various cultures. The differences among people, according to this theory, were attributable mainly to their varying racial background e.g., the Hottentots were considered one-step above the apes. South Africa has a legacy of polarised racial communities that still affect Africa not much less than the other continents with which Africa may be identified. Many of the political, social and economic patterns, structures and attitudes of racism that characterised the apartheid era continue to shape many of the experiences of life in South Africa today. One cannot pretend that racial discrimination, racial prejudice, racial stereotypes, xenophobia and other forms of racism no longer characterise the South African society. Despite rapid progress in race relations and the introduction of positive nondiscrimination and equity legislation in political level, a more systematic programme is required to transform race relations in ordinary people.